Gastric Juice-Based Genotypic Methods for Diagnosis of Helicobacter pylori Infection and Antibiotic Resistance Testing: A Systematic Review and Meta-analysis - Si, Xiao-Bei; Bi, De-Ying; Lan, Yu; Zhang, Shuo; Huo, Lin-Yu (Turkish Journal of Gastroenterology, 2021)
Background/Aims: To evaluate the diagnostic efficacy of gastric juice‐based genotypic methods for Helicobacter pylori detection and antibiotic resistance testing.Materials and Methods: We used electronic databases including Medline, Embase, Web of Science and the Cochrane Central Register of Controlled Trial for literature survey using keywords such as "gastric juice", "Helicobacter pylori" and their synonyms. The quality of the studies was assessed using QUADAS-2. Summary performance measures (sensitivity, specificity, positive predictive values, negative predictive values, diagnostic odds ratio, and area under the summary receiver operating characteristic curve) and HSROC curves were produced. In addition, fagan plots were applied to illustrate the relationship among the prior test probability, PLR/NLR, and posterior test probability.Result: Our study cohort comprised eight studies with 1235 participants (617 participants of H. pylori infection and 618 participants of non-H. pylori infection). Pooled sensitivity and specificity with a corresponding 95% confidence interval (CI) of gastric juice-based genotypic methods reflected values of 94% (95%CI, 86% - 98%) and 98% (95%CI, 85% - 100%), respectively. The global sensitivity and specificity of clarithromycin resistance were 92% (95%CI, 85% - 96%) and 90% (95%CI, 80% - 95%), respectively. Conclusion: Gastric juice-based genotypic methods can be used for diagnostic prediction of H. pylori infection as well as clarithromycin resistance testing.